A visualization framework for patient data and its environment - Ayyagari, Pavani (Kansas State University, 2010)
A Health Care System is targeted to provide well-monitored patient care. ‘A Visualization Framework for Patient data and its environment’ offers a broad portfolio of patient monitoring to help and improve patient care. ‘A Visualization Framework for Patient data and its environment’ is an application to monitor and analyze any patient’s activity visually through a period of time in conjunction with the surroundings aspects like the room temperature, status of lights in the room, etc. in a healthcare system. A set of sensors equipped with each patient record data, pertaining to the patient’s movement and location in addition to a few other sensor values like temperature and light sensors for recording the room temperature, status of lights in the room respectively. On accepting the activity time bounds as the input, the application retrieves the appropriate values from the database and displays the patient position as a continuous stream of images in association with a slider along with the temperature values. A floor map of the hospital, similar to a blueprint model, is portrayed along with graphical display of lights, in conjunction with the slider. The patient locations are depicted on the map by minute icons with a patient id associated with the each of the icons for identification purposes. Individual window frames for each patient, displaying a patient’s position, enable the user to customize monitoring to specific patients at any instance of time and thus keep track of every move of the patient over a considerate period of time. The locations of the patients on the map, the lights in the rooms depicted on the floor map, the patient position in the individual windows and the temperature are all in synchronization with the slider whose movement is a function of time. The application allows monitoring of values that correspond closely to real-time data values thus maximizing the scope of improvements in the patient’s progress. The application is implemented on a Java Platform using Swings and is expected to handle considerable amounts of data up to two days.
Keywords: Visualization; Framework; Graphical User Interface; Monitoring Patient Activity; Computer Science (0984)